2018
DOI: 10.5114/hpc.2018.76746
|View full text |Cite
|
Sign up to set email alerts
|

Social functioning of elderly people living in rural areas

Abstract: Authors' contributionWkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane -analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. Literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy SummaryBackground. The aim of this work was to assess social functioning of elderly people living in rural areas. Material and methods. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found that the level of loneliness among widowed older people was higher than older persons in other marital statuses [ 34 ]. Evidence also proved that widowed older people may possess low levels of social support from families and society [ 35 , 36 ], which indicates that their social capital may also be inadequate. Therefore, this study aimed to examine the association between social capital (BOC and BRC) and loneliness among the Chinese widowed older people, with regard to the rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the level of loneliness among widowed older people was higher than older persons in other marital statuses [ 34 ]. Evidence also proved that widowed older people may possess low levels of social support from families and society [ 35 , 36 ], which indicates that their social capital may also be inadequate. Therefore, this study aimed to examine the association between social capital (BOC and BRC) and loneliness among the Chinese widowed older people, with regard to the rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%